Visco-elastic systems as a quadratic eigenvalue problem - Forjaz, Maria Antónia (2017)
In viscous materials systems, time and stress dependent instabilities often occur. The evolution of visco-elastic systems under external stress has already been modeled by applying matricial dynamic equations comprehending elasticity and viscosity matrices. In this study we report a novel formulation for such kind of systems as a nonlinear quadratic eigenvalue problem evolving from an already defined adjacency matrix. A four mass-spring damped system is presented as case study.